2012
DOI: 10.1200/jco.2012.30.15_suppl.509
|View full text |Cite
|
Sign up to set email alerts
|

PI3K pathway (PI3Kp) dysregulation and response to pan-PI3K/AKT/mTOR/dual PI3K-mTOR inhibitors (PI3Kpi) in metastatic breast cancer (MBC) patients (pts).

Abstract: 509 Background: The role of PI3Kp dysregulation as a predictor of sensitivity to PI3Kpi is unclear. We aimed to evaluate the efficacy of PI3Kpi in two cohorts of MBC pts with assessable PI3Kp status. Methods: MBC pts treated in ≥3rd line with PI3Kpi were reviewed. PI3Kp status: (a) No dysregulation: PIK3CA wt and PTEN normal; (b) PI3Kp dysregulation: PIK3CA mutation (PIK3CAmut) or PTEN low (HScore≤50). Cohort A: pts treated with single agent PI3Kpi. Cohort B: pts treated with PI3Kpi in combination with hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…A retrospective review of patients with metastatic breast cancer treated with inhibitors of the PI3K/Akt/mTOR pathway reported that patients with PIK3CA mutations treated with a single agent did not have an increased TTP; however, when PI3K/Akt/mTOR inhibitors were combined with endocrine therapy, HER2-directed therapy or chemotherapy, the presence of PIK3CA mutations correlated with increased TTP compared with patients with wild type tumors [Oliveira et al 2012]. In the same analysis, the PTEN status did not seem to have any correlation with clinical outcome, which seems to confirm the results reported by Weigelt and colleagues.…”
Section: Biomarkersmentioning
confidence: 99%
“…A retrospective review of patients with metastatic breast cancer treated with inhibitors of the PI3K/Akt/mTOR pathway reported that patients with PIK3CA mutations treated with a single agent did not have an increased TTP; however, when PI3K/Akt/mTOR inhibitors were combined with endocrine therapy, HER2-directed therapy or chemotherapy, the presence of PIK3CA mutations correlated with increased TTP compared with patients with wild type tumors [Oliveira et al 2012]. In the same analysis, the PTEN status did not seem to have any correlation with clinical outcome, which seems to confirm the results reported by Weigelt and colleagues.…”
Section: Biomarkersmentioning
confidence: 99%
“…All studies published so far still have a very small number of cases and the results are suggestive at best. It has been shown, for instance, that a mutation in PI3KCA was associated with a poorer prognosis among patients receiving PI3K inhibition as monotherapy, while it was associated with a better prognosis among combination treatments with anti-hormonal therapy or chemotherapy [28].…”
Section: Breast Cancer-specific Mutations and Signal Pathwaysmentioning
confidence: 99%
“…In each case of response to therapy or stability, treatment was either continued until progression or chemotherapy discontinued and bevacizumab continued as maintenance treatment. Neither nab-paclitaxel nor ixabepilone exhibited an improvement in Prognose bei Patientinnen mit einer PI3K-Inhibition als Monotherapie, aber mit einer besseren Prognose bei Kombinationsbehandlungen mit Antihormontherapie oder Chemotherapie verbunden war [28]. In der FinHER-Studie wurden auch somatische Genmutationen in PI3K mit der Prognose und dem Therapieansprechen entsprechend dem Trasuzumab-Behandlungsstatus verglichen, jedoch konnte kein Zusammenhang mit der Prognose oder der Trastuzumab-Wirksamkeit gesehen werden [29].…”
Section: Chemotherapy In the Metastatic Settingunclassified